Peningkatan Pengetahuan Masyarakat Tentang Hipertensi Menggunakan Metode Cerdik (Ceramah dan Diskusi) di Kelurahan Ganti: Pengabdian Masyarakat - Basri; Rifka Adilla; Amia Armita; Fifi Febi Febiola Lauwa; Julia Angraini Pas; Laura Lawrensa Taruangi; Apriyani Adipu; Abdul Arafat; Gray Puspa Enjelis; Ali Akbar S Mbia; Sri Warni A. Djaana; Veronicha Septiyani Blake; Sariti; Sindi Auliya; Fajrah; Sri Mulyani (LPPM Universitas Widya Nusantara, 2025)
Hypertension is a major non-communicable disease and a leading risk factor for cardiovascular disorders, stroke, and kidney failure. Lack of public awareness and knowledge often hinders prevention and management efforts. This study evaluated the effectiveness of health education through lectures and group discussions in improving community knowledge about hypertension in Ganti Village, Banawa District, Donggala. A cross-sectional design with 17 participants was applied. Educational materials were delivered using leaflets and followed by interactive discussions. Knowledge was assessed using pre- and post-test questionnaires. The results showed a significant increase in knowledge: before the intervention, 64.7% had good knowledge, 29.4% moderate, and 5.9% poor; after counseling, all participants (100%) demonstrated good knowledge. These findings highlight that counseling with structured materials and active participation is effective in enhancing community understanding of hypertension. Continuous health education is recommended to support sustainable hypertension prevention and control.